Construct approximate dual g-frames in Hilbert spaces. Issue 2 (25th January 2021) - Guo, Qianping; Leng, Jingsong; Li, Houbiao
Abstract : In this paper, we first present some simple approaches to obtain dual and approximate dual g-frames. Then, we show that approximate dual g-frames are stable under some conditions. Finally, we give mainly a new characterization for approximate dual g-frames associated with given g-frames and bounded operators. Moreover, we prove that if two g-frames are close to each other, then we can find approximate dual g-frames associated with them which are close to each other.